PENGEMBANGAN MEDIA POWTOON BERBASIS KEARIFAN LOKAL KENDAL UNTUK MENINGKATKAN HASIL BELAJAR PPKN SEKOLAH DASAR - Muna Alawiyah; Novi Setyasto (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
This research is motivated by the limitations of media and learning resources in learning civic education material on the socio-cultural diversity of society. The purpose of this research is to develop powtoon media based on Kendal local wisdom and test its feasibility and effectiveness. This type of research uses Research and development (R&D) with the research subject of fifth grade students of SDN 1 Gonoharjo, Kendal district. Product trials were conducted in two stages with sampling techniques using purposive sampling techniques, namely small-scale product trials involving 9 students and large-scale product trials involving 24 students. Observation, interviews, documentation, questionnaires, and tests are data collection techniques used by researchers, and for data analysis techniques researchers use product feasibility analysis, initial and final data analysis consisting of T-tests and N-gain tests. The results showed through feasibility validation that powtoon media based on Kendal local wisdom was feasible to use as a learning media with a percentage of 100% media validation assessment, 96.4% material expert validation, 92.5% language expert validation, the three validations were included in the criteria very feasible. Kendal's local wisdom-based powtoon media is also effective in learning civic education as evidenced by the t-test whose results show a sig. (2tailed) value of 0.000 <0.05 then, ho is rejected and ha is accepted, which means that there is a significant difference between pretest and posttest learning outcomes in civic education learning through the powtoon media. The effectiveness of powtoon media is also reinforced through the n-gain test which shows an average increase of 0.626 with a difference of 35.83 with moderate criteria.